FINDING MEANING OF LIFE IN IMAM AL-GHAZALI'S CONCEPT OF MA'RIFATUN NAFS' THROUGH LOGOTHERAPY COUNSELING INTERVENTION - Ananda, Siti Dea; nurjannah, Nurjannah (INSTITUT AGAMA ISLAM NEGERI METRO, 2024)
Various variants of life problems make every human being ever in the phase of looking for the meaning of life. This raises many questions about how the meaning of life and the extent to which a person can find the meaning of life. This paper aims to examine in depth the logotherapy and ma'rifatun nafs' concept of Imam al-Ghazali in finding the meaning of life. There are two main issues answered in this study, namely how the concept of ma'rifatun nafs' Imam al-Ghazali and how the form of synergy of ma'rifatun nafs' with logotherapy intervention. This research is a qualitative research with literature review approach. Finding the meaning of life can be done with logotherapy intervention with a spiritual dimension that characterizes its implementation. In the process of providing logotherapy intervention, a person must first recognize himself. This is in line with the concept of ma'rifatun nafs' Imam al-Ghazali in finding the meaning of life. because of the similarity in finding the meaning of life so that the concept of ma'rifatun nafs' Imam al-Ghazali is recommended to be applied in providing logotherapy interventions to fill the spiritual dimension.